Controlled ovarian stimulation outcomes of fertility preservation procedures in newly diagnosed breast cancer patients: a retrospective study from a single-tertiary-IVF centre. (3rd April 2022) - Sahin, Gulnaz; Goker, Ege Nazan Tavmergen; Gokmen, Erhan; Yeniay, Levent; Acet, Ferruh; Zekioglu, Osman; Tavmergen, Erol
Abstract: The aim of this study was to evaluate the effectiveness of controlled ovarian stimulation (COS) using the letrozole-supplemented stimulation protocol in breast cancer (BC) patients prior to their cancer treatment. Sixty-one BC patients (Stages 0–3) who were referred to a university IVF unit for fertility preservation (FP) and underwent embryo and/or oocyte cryopreservation between 2008 − 2020 were included in this retrospective study. Time intervals between breast surgery and initial fertility consultation (IFC)/completion of FP procedures were evaluated. COS outcomes were assessed and compared between the early follicular phase (EFP) and the random-start (RS) protocols. The patients' mean age was 33.3 ± 4.9 years. The mean time interval between breast surgery and IFC was 20.6 ± 11 (day, mean ± SD) and from IFC to completion of FP procedure was 14.7 ± 5.3. Overall, 9.1 ± 5.9 mature oocytes were obtained, with a peak serum oestradiol level of 388 ± 358 pg/mL. The number of oocytes obtained (11.5 ± 9.3 vs. 10.9 ± 6.9, p = .9) and maturation rates (84.3 ± 17.5% vs. 89.2 ± 11.7, p = .5) were not statistically different between the EPF and RS protocols. The study results support that oocyte or embryo freezing can be performed effectively in a limited time period with letrozole-supplemented COS protocols before the initiation of oncological treatments in breast cancer patients. Impact statement: What is already known on this subject? Currently, embryo and oocyte freezing are considered the most established fertility preservation (FP) methods for newly diagnosed cancer patients. What do the results of this study add? This study reports the COS outcomes of newly diagnosed breast cancer patients for FP over a period of twelve years from a single IVF unit. The results support that a considerable number of oocytes can be harvested with letrozole-supplemented COS protocol, which appears to be an effective protocol for BC patients. What are the implications of these findings for clinical practice and/or further research? There is a need for additional studies evaluating long-term follow-up of patients with their pregnancy outcomes.